Whaam! : the art & life of Roy Lichtenstein - Rubin, Susan Goldman (Abrams Books for Young Readers, 2008)
Explores Roy Lichtenstein's work, life, and his groundbreaking influence on the art world. In Roy's long career as a teacher, artist, and innovator, he changed the way that people thought about art and how artists thought about their subjects.